Resíduos gerados nas agroindústrias da microrregião de Propriá e as práticas de gestão ambiental adotadas - Menezes, Carla Souza (2006)
In the current productive process of the agribusinesses residues are generated, that if thrown improperly to the environment, besides they cause environmental problems, they are constituted in source of waste of natural resources. The administration of those residues is made necessary, in way to contribute with the maintainable development of the microregion of Propriá, where most of the municipal districts is located in the area of the semi-arid sergipano. The objective of this study was to analyze the administration of the solid/liquid residues of those agribusinesses and to formulate proposed returned for the maintainable development. For if they classify descriptive and exploratory, with rising accomplishment (survey), sources of primary and secondary data were used. The primary data were collected through the use of the techniques of the interview semi-structured 87 agribusinesses close to, questionnaire close to ADEMA, and systematic observation. Already the secondary data were obtained through bibliographical and documental sources. Among the main results of this study, it can stand out that most of the researched agribusinesses is classified as small businesses, being tied the activities of improvement of rice, cassava and milk mainly. Regarding the productive process, it was observed that all of the researched agribusinesses, independently of the adopted technology, or carry, they generate some residue type in the stages of the productive process. Most of these residues is being thrown improperly to the environment, however little measured they were taken by agribusinesses to minimize the environmental impacts of their activities, above all, due to lack of perception of the interviewees good part, on the environmental impacts of their activities, besides the community s little pressure, and of fiscalization organs and environmental regulation. The conclusions of the study suggest management of the process, with use of tool of control quality for improvement and control of the productive process, in way to allow the implantation of System of Environmental Administration with the concepts of the cleanest production. The first efforts should be gone back to the stages in which the residues should be stored and/or treaties for use those in a new production line inside of the company, or commercialization through the bag of residues.